ANALISIS KONSERVASI ENERGI PADA SISTEM PENCAHAYAAN DAN SISTEM PENDINGIN DI KANTOR SEKRETARIS DAERAH KABUPATEN GARUT - Illahi, Sirli Nursabandi; Priatna, Edvin; Hiron, Nurul (Teknik Elektro Universitas Siliwangi, 2020)
Energy conservation in lighting systems and cooling systems aims to obtain optimal operation of energy usage without changing the function of the building, comfort and productivity of occupants, as well as considering aspects of environmental friendliness and cost. The results of observations in D and E buildings of the Garut Regional Secretary Office, almost all the rooms have lighting that does not appropriate the standard and humidity relative that exceeds the comfort factor of people in the room based on SNI. Based on the background of the problem, this study aims to look for conservation opportunities in lighting systems and cooling systems. The method used is an energy audit by calculating IKE, measuring the intensity of lighting and measuring temperature and humidity in some rooms. Based on the analysis results, the average IKE values in buildings D and E which are 1,1 kWh/m2/month and 2,54 kWh/m2/month are included in the highly efficient category based on Minister of Energy and Mineral Resources Regulation No. 13/2012. The energy conservation opportunity in this research is to redesign the artificial lighting system by replacing conventional TL lamps into LEDs and a total power of 2301,3 watts, then simulated in the DIALux software to get the assumption of average lux in accordance with the standard payback period of 4,5 years . For the cooling system, recalculating the heat load in occupied rooms is recommended for the replacement of air conditioners in conditioned rooms and the addition of AC in rooms that have not been conditioned with AC inverter and generated 6760 watts of power with a payback period of 27 months.Keywords: Energy Audit, Energy Consumption Intensity (IKE), Energy Conservation, Lighting Systems, Cooling Systems